HUBUNGAN PEER ATTACHMENT DENGAN FLOW AKADEMIK PADA SISWA SMA: STUDI PADA SMAN 1 X KOTO - Larasati, Suci; Firman, Firman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the relationship between peer attachment and academic flow among students of SMAN 1 X Koto. The study involved 177 students and employed the product moment correlation method to analyze the data. The results indicated a significant relationship between peer attachment and academic flow, with a correlation coefficient of 0.420 and a significance level of 0.000. This suggests a moderate relationship between the two variables, meaning that stronger peer attachment is associated with higher academic flow. Conversely, students with weaker peer attachment tend to experience lower academic flow. The findings are important as they show that social support from peers plays a significant role in enhancing students' focus and academic engagement. This study provides insights for educators and counselors to develop strategies that improve peer social support and promote better academic achievement.